Manajemen Perubahan Kurikulum Merdeka Berbasis Kepemimpinan Kepala Madrasah di MTs Nurul Huda Dau Malang - Muhamad Ardhani Latif; Shobihatul Fitroh Noviyanti; Naila Itsna Maulidah; Saidatus Salamah; Aulia Yunia Wati (Al-Kindi, 2026)
Leadership plays a crucial role in managing curriculum change, particularly in Islamic educational institutions that must balance national curriculum demands with their Islamic identity. This study aims to describe the role of principal leadership in managing the implementation of the Merdeka Curriculum at MTs Nurul Huda Dau Malang. This research uses a qualitative descriptive approach through in-depth interviews, observation, and documentation. Data analysis used the Miles and Huberman interactive model, while validity was ensured through source and technique triangulation. The findings reveal four main themes: principal leadership based on family values, visionary, and transparent; tiered socialization from supervisors to teachers coordinated by the vice principal without a dedicated team; P5 implementation with entrepreneurship and diversity themes that increased student creativity and self-confidence; and mandatory teacher training twice a year with monthly learning evaluations. This study concludes that adaptive and value-based principal leadership is the main foundation for the success of Merdeka Curriculum change management in Islamic educational institutions.